RESTRICTIVE MEASURES OF CRIMINAL LEGAL NATURE: INDIVIDUAL CONSIDERATIONS REGARDING THE REGULATORY DEFINITION OF THE CAUSAL COMPLEX OF THEIR IMPLEMENTATION AND GENERAL PRINCIPLES OF APPLICATION (Bulletin of criminological association of Ukraine, 2022)
The article is devoted to the study of the causal complex of restrictive measures of criminal law and general principles of their application and development on this basis of their own generalized conclusions aimed at further development of scientific understanding of the prerequisites and grounds for their implementation and improvement of law enforcement practice through compliance with certain rules or criteria.
Keywords: restrictive measures, domestic violence, abuser, victim of domestic violence, interests of the victim.